Vaginal birth after a previous caesarean section functional vs static marker - Omole-ohonsi A (Ibom Medical Journal, 2011)
Background: Primary caesarean section increases the chances of repeat caesarean section. In our society, there is a high prevalence of teenage pregnancy which is a high risk factor for primary caesarean section due to cephalopelvic disproportion. Continuing growth of these adolescents and their pelvic bones, makes their pelves bigger in the next pregnancy with a favourable prospect of vaginal delivery. A reliable method of assessment of these patients to identify those who are suitable for trial of labour is invaluable. Aims: This study was aimed at assessing the reliability of the Head Fitting Test (HFT) compared with Antepartum X-ray Pelvimetry (AXRP) in selecting patients for trial of labour after primary caesarean section. Methods: This was a comparative prospective study of 300 women with a previous lower uterine segment caesarean section who were delivered at Aminu Kano Teaching Hospital, Kano, Nigeria, over a six year period (1998-2003). Result: The sensitivity of HFT was 97.0%, specificity was 96.1%, positive predictive value was 98.0% and negative predictive value 94.2%. The sensitivity of AXRP was 34.7%, specificity 24.0%, positive predictive value 31.3% and negative predictive value 26.9%. The sensitivity of PXRP was 49.3%, specificity 18.7%, positive predictive value 37.8% and negative predictive value 26.9%. Conclusion: HFT was found to be a better method than AXRP in selecting the women with a previous caesarean section, who were suitable for trial of labour and vaginal delivery.